2003
DOI: 10.2118/03-02-02
|View full text |Cite
|
Sign up to set email alerts
|

Full Scale VAPEX Process-Climate Change Advantage and Economic Consequences A

Abstract: With the VAPEX process, combinations of vaporized solvents are injected into heavy oil and bitumen reservoirs for in situ recovery of the oil. The oil is diluted with the solvent, which reduces the viscosity so the oil drains by gravity to a horizontal production well. The VAPEX process has the potential to greatly reduce the greenhouse gas emissions for oil sands and heavy oil recovery since it is a non-thermal process that does not require the reservoir to be heated with, for example, steam. The Petroleum Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Nevertheless, an economic constraint for applying these thermal-based oil recovery processes arises if the high costs of steam generation and the excessive heat losses into thin formations are considered. Moreover, source water supply, greenhouse gases emission and produced water treatment make other enhanced oil recovery techniques more economically viable and environmentally friendly as well (Luhning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an economic constraint for applying these thermal-based oil recovery processes arises if the high costs of steam generation and the excessive heat losses into thin formations are considered. Moreover, source water supply, greenhouse gases emission and produced water treatment make other enhanced oil recovery techniques more economically viable and environmentally friendly as well (Luhning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early demonstrations of its effectiveness Mokrys, 1991, 1993), Vapex has undergone substantial advancement from laboratory scale studies to pilot plant investigations, and commercial projects (Turta and Singhal, 2004). Principal reasons are the non-thermal nature of Vapex, its environ mental friendliness, low capital and operating costs, and its suitability to thick as well as frequently occurring thin heavy oil and bitumen reservoirs relative to other recovery processes (Luhning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Luhning et al (2003) did a comprehensive literature on the environmental advantages of VAPEX and they concluded that due to the in situ upgrading that takes place during the VAPEX process, there will be less asphaltene in the produced oil. This means less energy is needed for the transportation of heavy oil in pipelines as well as less maintenance costs for the pipelines and facilities.…”
Section: Introductionmentioning
confidence: 99%